Considerations in Forensic Psychiatric Reports According to Supreme Court Reversal Decisions on Juvenile Delinquents: Forensic Psychiatric Reports of Juvenile Offenders - Bertizlioğlu, Osman; Çelik, Cemil (The Bulletin of Legal Medicine, 2023)
Objectives: It is aimed to determine the causes of supreme court reversal in the field of forensic psychiatry on Juvenile Delinquents and identifying to issues be considered while preparing a report.Materials and Methods: From website of the Supreme Court https://karararama.yargitay.gov.tr/YargitayBilgiBankasiIstemciWeb/,  691 reversal decisions on forensic psychiatric issues regarding juvenile delinquents were examined by using the words: “child psychiatry”, “child and adolescent mental health”, “child at the age of discretion”, “mental health, child”, “perceiving the legal meaning and consequences, directing their behaviour” and “the child delinquent”.Results: It was determined that the most common reason for reversal in the evaluation of criminal responsibility by age in children (n:208, 36.3%) was the absence of social examination report or forensic psychiatric report, used of reports prepared for past crimes in the trial process, the second most common reason (n:169, 29.5%) was the reports which weren’t prepared duly and found insufficient in terms of content. In the evaluation of criminal responsibility due to mental illness, it was seen that the most common reason for reversal (n: 154, 40.5%) was that although mental illness was stated in the history of psychiatric illness, insufficient investigation was carried out on this subject, and that the second most common reason for reversal was (n: 130, 34.2%) the decision was made before delegation report was received.Conclusion: It is important for the prepared reports to contain complete, reasoned and clear opinions, to prevent grievances due to the judicial process, and to protect the best interests of the child.
Keywords: Discretion; Criminal Responsibility; Forensic Report; Juvenile Offender; Supreme Court